2016
DOI: 10.1002/jmri.25518
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic gadoxetic acid uptake as a measure of diffuse liver disease: Where are we?

Abstract: 3 J. Magn. Reson. Imaging 2017;45:646-659.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 112 publications
(147 reference statements)
1
53
0
Order By: Relevance
“…17 Several studies have examined whether the uptake of a liver-specific contrast agent in the liver parenchyma is correlated with liver function and the degree of liver fibrosis, yet only a few have used histopathology data as the reference standard. Gadoxetic acid is a widely used liver-specific MRI contrast agent with combined extracellular and hepatocyteselective properties.…”
Section: Discussionmentioning
confidence: 99%
“…17 Several studies have examined whether the uptake of a liver-specific contrast agent in the liver parenchyma is correlated with liver function and the degree of liver fibrosis, yet only a few have used histopathology data as the reference standard. Gadoxetic acid is a widely used liver-specific MRI contrast agent with combined extracellular and hepatocyteselective properties.…”
Section: Discussionmentioning
confidence: 99%
“…Suboptimal HBP is common in patients with impaired hepatobiliary function. A suboptimal HBP is characterized by liver parenchyma that is iso‐ or hypointense to the hepatic blood vessels, and by lack of excretion of contrast into the biliary tree and persistent contrast within the spleen . Excretion of gadoxetate disodium may be decreased due to a combination of diminished functional liver, cholestasis, or downregulation of or competition for transporters .…”
Section: Pitfalls Of Gadoxetate Disodium Usementioning
confidence: 99%
“…A suboptimal HBP is characterized by liver parenchyma that is iso-or hypointense to the hepatic blood vessels, and by lack of excretion of contrast into the biliary tree and persistent contrast within the spleen. [60][61][62] Excretion of gadoxetate disodium may be decreased due to a combination of diminished functional liver, cholestasis, or downregulation of or competition for transporters. 63,64 The sensitivity for liver lesion detection and subsequent characterization can be reduced when the HBP is suboptimal 65 (Fig.…”
Section: Suboptimal Hbp Imaging: Causes and Effectmentioning
confidence: 99%
“…3 Several MRI methods have been used to assess liver fibrosis and inflammation severity, including magnetic resonance (MR) elastography, 21 diffusion-weighted MRI, 22 MR perfusion imaging 23 and gadoxetic acid-enhanced MRI. 24 Recently, it has been shown that susceptibility-weighted MRI, by combining phase and magnitude information, is also a promising method for the staging of liver fibrosis. 25,26 Susceptibility-weighted MRI, however, remains semi-quantitative.…”
mentioning
confidence: 99%